Optimization of flavanonols heterologous biosynthesis in Streptomyces albidoflavus, and generation of auronols - Magadán-Corpas, Patricia; Ye, Suhui; Braune, Annett; Villar, Claudio J.; Lombó, Felipe (Frontiers in Microbiology, 2024)
Aromadendrin and taxifolin are two flavanonols (derived from the precursor naringenin) displaying diverse beneficial properties for humans. The carbon skeleton of these flavonoids may be transformed by the human gastrointestinal microbiota into other compounds, like auronols, which exert different and interesting biological activities. While research in flavonoids has become a certainly extensive field, studies about auronols are still scarce. In this work, different versions of the key plant enzyme for flavanonols biosynthesis, the flavanone 3-hydroxylase (F3H), have been screened for selecting the best one for the de novo production of these compounds in the bacterial factory Streptomyces albidoflavus UO-FLAV-004-NAR, a naringenin overproducer strain. This screening has rendered 2.6 µg/L of aromadendrin and 2.1 mg/L of taxifolin final production titers. Finally, the expression of the chalcone isomerase (CHI) from the gut bacterium Eubacterium ramulus has rendered a direct conversion (after feeding experiments) of 38.1 % of (+)-aromadendrin into maesopsin and 74.6 % of (+)-taxifolin into alphitonin. Moreover, de novo heterologous biosynthesis of 1.9 mg/L of alphitonin was accomplished by means of a co-culture strategy of a taxifolin producer S. albidoflavus and a CHIexpressing Escherichia coli, after the observation of the high instability of alphitonin in the culture medium. This study addresses the significance of culture time optimization and selection of appropriate enzymes depending on the desired final product. To our knowledge, this is the first time that alphitonin de novo production has been accomplished.